Product Marketing With Social Media And Strengthening Identity Through Packaging Branding - Nugraha, Putu Gede Surya Cipta (International Journal of Community Service Learning, 2021)
Currently, entrepreneurs are pursuing various kinds of strategies to expand their marketing share and strengthen their business identity in the midst of new products that have emerged by presenting updates in accordance with existing interests in the market. The partner in this community service activity is Mrs Sukarini, a donut snack entrepreneur from Kukuh Village, Tabanan Regency, which is usually consumed by children and adults as well as for religious activities. Currently, businesses owned by partners are experiencing obstacles in expanding market share, branding on donut packaging which is still relatively simple and the need to add flavors to donuts. The solution that can be given is to socialize and assist digital marketing and packaging branding. The results of the evaluation with partners in this community service activity were that the donut flavor variants that were given also received a positive response from consumers which at the same time resulted in an increase in donut sales compared to the previous month, thus increasing the business profit figures. Marketing through social media and branding also has a big role because Mrs. Sukarini gets orders for donuts over the phone for religious ceremonies in the local area. In addition, partners are very happy to get additional knowledge about digital marketing and branding that can provide a positive aura for the progress of their business. Activities run well, smoothly and are felt to provide benefits to partners in addition to knowledge but also in the form of strategies to build identity, build consumer trust and increase the selling power of donut snacks.